PENETAPAN KADAR ALKALOID DARI EKSTRAK ETANOLIK BUNGA KEMBANG SEPATU (Hibiscus rosa-sinensis L.) - Mimiek Murrukmihadi; Subagus Wahyuono; Marchaban Marchaban; Sudibyo Martono (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Kembang sepatu flower (Hibiscus rosa-sinensis L.) was fractionally used as expectorant. Based on Bioassay Guided fractionation, an active fraction was separated, and the fraction was identified is Alkaloid was the major compound based on TLC analysis. Viscosity value measured by viscometer was used as a Bioassay model of expectorant activity in vitro and asetyl cysteine was used as positive control. Alkaloid content determination of the ethanolic extract was measured by TLC-Densitometric compared with standard curve of isolated alkaloid as the selected marker (Y=12.1360X+2901.4474). The alkaloid content in the ethanolic extract was determined as 2.35 ± 0.67 %.